Impact of maternal Bifidobacterium breve M-16V and scGOS/lcFOS supplementation during pregnancy and lactation on the maternal immune system and milk composition - Sáez-Fuertes, Laura; Kapravelou, Garyfallia; Grases-Pintó, Blanca; Massot-Cladera, Malen; Bernabeu, Manuel; Knipping, Karen; Garssen, Johan; Bourdet-Sicard, Raphaëlle; Castell, Margarida; Rodríguez-Lagunas, Maria José; Collado, Maria Carmen; Pérez-Cano, Francisco José (Frontiers in Immunology, 2024)
Maternal synbiotic supplementation during pregnancy and lactation can significantly influence the immune system. Prebiotics and probiotics have a positive impact on the immune system by preventing or ameliorating among others intestinal disorders. This study focused on the immunomodulatory effects of B. breve M-16V and short chain galacto-oligosaccharides (scGOS)/long chain fructooligosachairdes (lcFOS), including systemic and mucosal compartments and milk composition. Lewis rats were orally administered with the synbiotic or vehicle during pregnancy (21 days) and lactation (21 days). At the weaning day, small intestine (SI), mammary gland (MG), adipose tissue, milk, mesenteric lymph nodes (MLN), salivary gland (SG), feces and cecal content were collected from the mothers. The immunoglobulinome profile showed increased IgG2c in plasma and milk, as well as elevated sIgA in feces at weaning. The supplementation improved lipid metabolism through enhanced brown adipose tissue activity and reinforced the intestinal barrier by increasing the expression of Muc3, Cldn4, and Ocln. The higher production of short chain fatty acids in the cecum and increased Bifidobacterium counts suggest a potential positive impact on the gastrointestinal tract. These findings indicate that maternal synbiotic supplementation during gestation and lactation improves their immunological status and improved milk composition.